Patrimônio arquitetônico de Estrela, RS: diagnóstico para preservação - Schnack, Andrea Cristina (2012)
This dissertation presents the research performed on the county of Estrela, RS, over the year of 2010, which goal was to inventory the architectonic patrimony still existent in the town. The approach of this research is the field study. Town s residents, historians and experts in the county history were interviewed with the purpose the edifications collection to be the most complete as possible. The final collection pointed out forty one edifications that were cataloged and registered in standard record sheets, so resulting in an inventory of the architectonic patrimony of Estrela.